Pengaruh Packaging Produk Terhadap Keputusan Pembelian Konsumen Di Industri Makanan (Literatur Review Manajemen Pemasaran) - Zed, Etty Zuliyawati; Febriansah, Achmad Eka; Primayanti, Meita; Aryani, Fita; Dewi, Vira (Innovative: Journal Of Social Science Research, 2025)
The product packaging is one of the crucial elements in marketing strategy, especially in the fast-food industry, such as kebabs. This study aims to analyze the packaging of Kebab Alibaba products from the perspective of design, functionality, and its impact on consumer perception. Kebab Alibaba, as one of the popular kebab brands in Indonesia, utilizes packaging designed to capture attention, maximize branding, and ensure product quality. Our findings reveal that Kebab Alibaba’s packaging design emphasizes a combination of bright colors and visual elements that reflect the brand’s identity. The materials used demonstrate attention to sustainability aspects, employing eco-friendly materials that are resistant to oil and heat. Information included on the packaging, such as the halal logo, brand, and contact details, helps boost consumer trust. Additionally, the shape and functionality of the packaging are considered practical and ergonomic, offering a positive experience for consumers. The study results indicate that Kebab Alibaba’s product packaging serves not only as a protective layer but also as an effective communication tool for building brand image and influencing consumer purchase decisions. This research provides valuable insights for food industry players in developing effective and consumer-oriented packaging.